A banana republic? The effects of inconsistencies in the counting of votes on voting behavior - Niklas Potrafke; Felix Roesel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
We examine whether local inconsistencies in the counting of votes influence voting behavior. We exploit the case of the second ballot of the 2016 presidential election in Austria. The ballot needed to be repeated because postal votes were counted carelessly in individual electoral districts (“scandal districts”). We use a difference-indifferences approach comparing election outcomes from the regular and the repeated round. The results do not show that voter turnout and postal voting declined significantly in scandal districts. Quite the contrary, voter turnout and postal voting increased slightly by about 1 percentage point in scandal districts compared to nonscandal districts. Postal votes in scandal districts also were counted with some greater care in the repeated ballot. We employ micro-level survey data indicating that voters in scandal districts blamed the federal constitutional court for ordering a second election, but did not seem to blame local authorities.
Keywords: D72; D02; Z18; P16; 330; Elections; trust; political scandals; administrative malpractice; counting of votes; voter turnout; populism; natural experiment